APAKAH AKUNTABILITAS, TRANSPARANSI DAN PENGENDALIAN INTERNAL LAPORAN KEUANGAN MEMPENGARUHI KEPERCAYAAN DONATUR YAYASAN SOSIAL? : Abstrak - Kusmaeni, Emi; Syahrenny, Nenny (Faculty of Economics and Business University of Mataram, 2024)
Donor loyalty can occur because they trust in the social foundation to manage the funds they receive. The large amount of funds received is likely to cause misuse by interested parties. Several variables have been tested that could influence their trust as donors. Therefore, this research aims to analyze the influence of accountability, transparency, and internal control of financial reports on the trust of Social Foundation donors. A total of 98 samples were obtained by distributing questionnaires online. The test results show a significant positive effect of accountability and internal control of financial reports on donor trust, but transparency does not provide substantial results. The results of this research imply that social foundations can implement adequate accountability and internal control of financial reporting to increase donor trust.